Sources of stress among human resource practitioners : a study of the inter-relationship between career orientation, role stress and burnout : an investigation into sources of work-related stress in a sample of human resource practitioners in KwaZulu-Natal. - Legg, Ronald Leslie. (2012)
Human Resource Management (HRM) has undergone significant changes during the past twenty-five to thirty years in response to the demands made upon the Human Resource function. With the change in emphasis in HRM has come the need for human resource practitioners (HRPs) to adapt to the new demands made upon them to contribute directly to the bottom line success of their organisations It is argued that HRM is inherently ambiguous, attempting to meet both the needs of the business and the individual employee. This places pressure on HRPs to become "specialists in ambiguity" as they attempt to meet the demands of key stakeholders in the enterprise. The emphasis in the role of the HRP, has moved historically, from that of a welfare officer to that of a fully fledged member of the management team, held equally responsible for the success of the operation. As with most professions today, a price is exacted for participation in modem organisations in the form of increased work-related stress. Considerable research has been undertaken over the past thirty years into work-related stress among many professions~ but no identifiable, in depth studies into sources of work-related stress among HRPs were located. The significant shift that has taken place in the role of HRPs, from their original welfare orientated function, to the current role emphasis on contributing to direct bottom line success, provides the context for the increase in work related stress levels experienced by some HRPs. The study investigates the links between the career orientation of HRPs, role stress factors and burnout in an attempt to identify sources of stress among a sample of human resource practitioners drawn from the greater Durban area and the KwaZulu Natal coastal region. The report is diagnostic and not prescriptive in attempting to ascertain coping skills for stressed HRPs. The study model posits a juxtaposition between those HRPs who are "service" orientated with those who are "managemeng' orientated. The purpose is to establish in the current corporate environment, whether those who are more service orientated, would suffer greater work-related stress, in contrast to those who are more "management" orientated, who were conceived of as experiencing less work-related stress. No strong links are revealed between "service" and "general management' and Role Stress or Burnout. The combined effects of role stress and burnout are conceived in the study to illustrate work related stress. In contrast to the original study model, two other findings of significance emerged. Those HRPs who were entrepreneurially orientated showed the highest levels of workrelated stress. And, those who were technical/functional orientated were least likely to be affected by role stress and burnout. These findings are important in light of the current call for HRPs to be entrepreneurial and innovatively creative. Yet these HRPs reveal the greatest possibility of experiencing role stress and burnout. In contrast, those HRPs whose orientation is technical and functional are found to reveal the least possibility of suffering from work-related stress. These findings lead to a new paradigm revealing the presence of a different dilemma and tension for HRPs. Within the demand for a total business focus on the part of HRPs and HRM, emerges a tension between the more stressful entrepreneurial and innovative role and the more stable technical and functional role also demanded by the organisation. The study suggests that the ambiguity in HRM in practice presents itself in terms of dilemmas and contrasts with which the HRPs has to live. Role ambiguity and role overload appear to contribute most to the possibility of burnout. Role ambiguity has its origin in the very nature of HRM, which is shown to be inherently ambiguous. Role overload among management, is observed more as part of the nature of the modern work environment, whereas role ambiguity emerges as a feature of the nature of HRM. Role conflict is explained mostly as a normal element in the HRPs job of balancing competing demands in the work place. The ambiguous nature of HRM and the uncertainties which it generates adds to the work-related source of stress and leads to HRPs having to become "specialists in ambiguity". Role stress factors, rather than career orientation elements are shown to be the leading contributors to the possibility of increased levels of burnout The findings have implications for the selection and training of HRPs. The contemporary emphases require HRPs to balance a tough minded business focus with acceptable innovate approaches to the organisation's human resources and excellent ongoing functional services. This balancing of ambiguities needs to be accompanied by a sensitivity to people, without becoming the subject of role stress and raised levels of burnout. === Thesis (Ph.D.)-University of Natal, Durban, 2002.